Penyebab Fraud pada Perusahaan di Kota Banjarmasin - Suzi Suzana; Tina Lestari (Jurnal Bisnis dan Ekonomi, 2019)
Fraud in the company will most likely be encountered given that companies in general have many divisions. This study aims to determine how employees' perceptions in private companies in the city of Banjarmasin about fraud and how much influence the Pressure, Opportunity and Rationalization variables have on fraud prevention. The method used in this study is purposive sampling with criteria for employees who have influence in committing fraud, including: namely the head of the finance department (head of goods / services inventory), head of cash disbursements, and cash receipts (cashiers)) and staff. Samples taken in the study amounted to 40 people (from 10 companies with a total of 65 respondents). The results showed the first hypothesis (H1) could be accepted, where the value of Fcount was greater than Ftable. The results of testing the second hypothesis (H2) show the calculated value of the pressure variable, the opportunity variable and the rationalization variable, greater than the value of the table so that it can be concluded that only the opportunity variable has a partial effect on fraud (fraud) so that the second hypothesis is accepted.